Social Systems Structure, Job Design, and Growth Need Strength: A Test of a Congruency Model - Pierce, Jon L.; Dunham, Randall B.; Blackburn, Richard S. (Academy of Management Journal, 1979)
An eight cell congruency framework for social system structure (mechanistic-organic), job design (simple-complex), and employee growth need strength (low-high) was used to predict employee satisfaction, motivation, and performance, As expected, employee satisfaction was highest for persons in the organic-complex-high condition. Two way interaction effects (social system structure ? job design and job design ? growth need strength) also were found to be significant.